Toward Quantitative in vivo Label-Free Tracking of Lipid Distribution in a Zebrafish Cancer Model - Andreana, Marco; Sturtzel, Caterina; Spielvogel, Clemens P.; Papp, Laszlo; Leitgeb, Rainer; Drexler, Wolfgang; Distel, Martin; Unterhuber, Angelika (Frontiers in Cell and Developmental Biology, 2021)
Cancer cells often adapt their lipid metabolism to accommodate the increased fatty acid demand for membrane biogenesis and energy production. Upregulation of fatty acid uptake from the environment of cancer cells has also been reported as an alternative mechanism. To investigate the role of lipids in tumor onset and progression and to identify potential diagnostic biomarkers, lipids are ideally imaged directly within the intact tumor tissue in a label-free way. In this study, we investigated lipid accumulation and distribution in living zebrafish larvae developing a tumor by means of coherent anti-Stokes Raman scattering microscopy. Quantitative textural features based on radiomics revealed higher lipid accumulation in oncogene-expressing larvae compared to healthy ones. This high lipid accumulation could reflect an altered lipid metabolism in the hyperproliferating oncogene-expressing cells.